A NEW APPROACH IN VISUALISING HUMAN EMOTIONS USING BRAINWAVE-DRIVEN GENERATIVE ART - Lee Kin Keong; Jolaina M. Nasseri, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This paper delves into the exciting potential of real-time generative art as a powerful tool for visualizing emotion-based data, especially within creative collaborations. The research specifically narrowed on generative art, affective data, and creative teamwork. The main aim is to figure out just how generative art can effectively capture the intricate nature of human emotions and stand as a truly valid method for data visualization. A qualitative approach is chosen in getting participants involved in a self-tracking process. An electroencephalogram (EEG) device is used, specifically the Muse 2 headband, to get real-time visualizations of emotions. The data collected included brainwave activity and reflections on personal life events. Focusing on two key emotions: enjoyment and sadness, using text to stir up those personal experiences. The different brainwave frequencies, Alpha, Beta, Delta, Theta, and Gamma were then mapped directly to specific visual parameters of a 3D torus shape. These generative visuals can really be used as a fantastic data visualization method for some deep analysis into human mental well-being. Generative art can indeed capture a wide array of emotions and provides real-time visualizations of complex data without the removal of data noise. This research clearly showed that enjoyment and sadness each have its own distinct visual characteristics, which are reflected in the motion and visual qualities of the generated art. Crucially, the generative system actually considers that data noise instead of removing it, giving a much more authentic representation of emotions. Participants had heightened awareness and concentration while collaborating creatively. Ultimately, this research concludes that real-time generative art is a super effective way to visualize data and capture the intricate complexity of human emotions. By using raw brainwave data, the creation of unique visualizations of personal experiences without needing verbal or written explanations. This method truly offers a deeper understanding of emotions, which is vital for assessing mental well-being.